Die regionale Entwicklung der USA im Umbruch: Die Umkehr traditioneller Wachstumstrends in den siebziger Jahren - de Lange, Norbert (ERDKUNDE, 1986)
The regional development of the USA in the 1970s was characterized by major changes in economic and population growth. The calculation of growth figures reveals the contrast between the Northeast and the South and West: Since the 1940s the states of the traditional manufacturing belt show the smallest (relative) increase, whereby this trend already appeared in the past decades. In contrast Oklahoma, Arkansas, Kentucky, Tennessee, North and South Carolina, Mississippi, and Alabama have had a population growth above the national average for the first time, e.g. Texas and Florida even showed higher rates in former decades. The migration to the South was decisive for the different growth patterns: the south gave up its historical function of an outmigration area. The black population also participated in this migration and thus the historical exodus of the South was reversed. The West of the USA remained an influx area in the 1970s. Most important for the migration to the South was the increasing economic attraction of the South. While the traditional industries in the manufacturing belt were in a severe crisis, the South proved to be the (most) favourable region for new plant facilities, whereby Texas leads the South. Important factors in site selection include productivity of workers, community receptivity, efficient trans portation facilities, and tax considerations. These trends seem to be constant for the five years following 1981. The product cycle model can be used as a conceptual framework for the decentralisation of production, which is spatially interpreted as a core-periphery realignment process.